A case series study on exploring the role of HLA B27 among patients with retinitis pigmentosa and uveitis and short-term treatment response - M. Viswanathan; O. Zborovska; O. Y. Jones; V. Kolesnichenko; O. Dorokhova (Journal of Ophthalmology)
Purpose. We present a case series of retinitis pigmentosa associated with uveitis and share our clinical observations and insights on this co-occurrence. Materials and methods. This prospective, non-controlled case series included 7 patients with retinitis pigmentosa (14 eyes) who presented with concurrent signs of uveitis. Results. Among 173 patients with retinitis pigmentosa, 7 (4 males, 3 females) presented with signs of intermediate uveitis; 3 of them also had mild anterior uveitis. No sex predilection was observed. The mean age at uveitis diagnosis was 26.9 years (range 19–37). RP had been diagnosed more than 10 years earlier in 4 patients, 3 years earlier in 1 patient, and 2 years earlier in another; only 1 patient was diagnosed with both RP and uveitis during the current study. In addition to typical RP features, patients showed vitreous cells graded 1+ to 2+, and vitreous haze of 0.5+ to 1+. Cystoid macular edema was found in 5 patients. None reported acute onset of floaters, blurred vision, or central vision loss, and no systemic complaints were recorded. HLA-B27 positivity was identified in 5 patients (2 males, 3 females); 2 of them were subsequently diagnosed with low-activity ankylosing spondylitis, while the others were classified as having HLA-B27-associated uveitis. The remaining 2 patients were considered to have either idiopathic uveitis or significant inflammatory activity related to RP. All patients received anti-inflammatory treatment. Conclusions. The potential association with HLA-B27 should be taken into account in RP patients presenting with signs of anterior or intermediate uveitis, regardless of sex or the absence of acute uveitis symptoms and systemic manifestations.